How Mycobacterium tuberculosis drug resistance has shaped anti-tubercular drug discovery - Bhagwat, Amala; Deshpande, Aditi; Parish, Tanya (Frontiers in Cellular and Infection Microbiology, 2022)
Drug resistance is an increasing problem for the treatment of tuberculosis with currently available antibiotics. The prevalence of clinical isolates with pre-existing resistance needs to be considered in any drug discovery program. Non-specific mechanisms of resistance such as increased efflux or decreased permeability need to be taken into account both in developing individual drug candidates and when designing novel regimens. We review the different approaches to develop new analogs or improve efficacy of existing drugs and to delay the appearance of clinical resistance using combinations. We also discuss the need to fully characterize mechanisms of resistance to ensure that novel drugs will be clinically effective.